Continuous antibody purification using precipitation: An important step forward. Issue 6 (7th April 2014) - Velayudhan, Ajoy
Abstract Recent advances in cell culture have reduced upstream costs, and made downstream processing the more expensive component of biologics manufacturing. Within downstream processing, the chromatographic steps have usually been the most expensive, on the one hand because chromatographic steps are traditionally run in batch mode and on the other because resins are typically more expensive per unit mass of product than other bioproduct‐contact materials [1, 2]. There have been many attempts to consider alternatives to chromatography [3, 4], but the comparatively high resolution of chromatography, combined with the bioprocess industry's wealth of experience in using the various chromatographic modes, have made it hard to replace in a manufacturing setting. In this issue of Biotechnology Journal Hammerschmid et al. [5] make several original contributions to this discussion.